The Role of Response Perceptions in Couples' Ongoing Cancer-Related Disclosure. Issue 9 (29th July 2019) - Magsamen-Conrad, Kate; Venetis, Maria K.; Checton, Maria G.; Greene, Kathryn
ABSTRACT: In efforts to better understand the intricate nature of response, we tested a four-dimension structure of response patterns (measured as support, reciprocity, emotional reaction, and avoidance) as well as four single dimension models within the context of couples managing cancer. All models incorporate dyadic data, including both patient and partner perceptions that relational quality influences response patterns, and response patterns influence ongoing disclosure (measured as breadth and depth). Participants were 95 dyads in which one partner had been diagnosed with cancer. We conducted multilevel analyses using an actor-partner interdependence model. Results supported the four-dimension model as well as individual dimension models. All response types predict within person disclosure. However, only reciprocity predicts the other person's disclosure, and only patient's reports of partner reciprocity predict partner disclosure.